The role of academic institutions as a catalyst in strategic human resource development and green growth in Panay Island, Philippines experiences and lessons - Teodisio, April Dream Rico (2009)
The role of academic institutions in socio-economic and political reforms has been taken for granted in many countries including the Philippines. A shift from purely classroom instruction to actualization of classroom theories has been instituted in the Master in Public Administration (MPG) graduate program of West Visayas State University Philippines. With focus in mitigating climate change and attaining "green growth" in the region, the University through its MPG students' environment education has instituted a more creative and experiential approach. Through the auspices of the MPG class, three island barangays (villages) were adopted by the University. In these barangays, instructional materials on environment education were provided with the purpose of providing early exposure and training to the students in identifying environmental and other related issues. Advocacy for environment and good governance was done to advance the call to protect the environment and promote good governance. As advocates, various forums on electrical reforms, climate change, poverty alleviation, and empowerment of barangay officials were held. A mass-based approach through University partnership was effected to minimize poverty-related problems among farmers and fisherfolks engaged in destructive farming and fishing practices. Participation of stakeholders to assure "green growth" in the region was done through linkages and networking.
Keywords: Public administration -- Study and teaching -- Western Visayas; Public administration education; West Visayas State University